2000
DOI: 10.1038/sj.onc.1203812
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the NF-κB pathway by Caspase 8 and its homologs

Abstract: Caspase 8 is the most proximal caspase in the caspase cascade and has been known for its role in the mediation of cell death by various death receptors belonging to the TNFR family. We have discovered that Caspase 8 can activate the NF-kB pathway independent of its activity as a pro-apoptotic protease. This property is localized to its N-terminal prodomain, which contains two homologous death e ector domains (DEDs). Caspase 10 and MRIT, two DEDs-containing homologs of Caspase 8, can similarly activate the NF-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
193
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(209 citation statements)
references
References 45 publications
14
193
0
2
Order By: Relevance
“…14,17 To test this we examined degradation of IkB in response to TNF. WT, caspase-8 À/À , and FLIP À/À MEFs were treated with TNF for various time periods and IkB levels were determined by western blotting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…14,17 To test this we examined degradation of IkB in response to TNF. WT, caspase-8 À/À , and FLIP À/À MEFs were treated with TNF for various time periods and IkB levels were determined by western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17] It has been reported that FLIP and caspase-8 are sometimes necessary for activation of NF-kB, or are capable of activating NF-kB when overexpressed. 13,14 For example, Hu et al 13 found that overexpression of FLIP or caspase-8 caused potent activation of an NF-kB reporter in 293HEK cells, and Chaudhary et al 14 found that overexpression of caspase-8 or FLIP in 293T or MCF7 cells activated NF-kB reporters. Interestingly, both groups found that, although catalytically inactive forms of caspase-8 were still able to induce NF-kB, and neither viral nor synthetic caspase inhibitors could block this, these inhibitors were able to block NF-kB induction by overexpression of FLIP, suggesting that proteolysis of FLIP by caspase-8 is not required for it to activate NF-kB, but might be necessary for caspase-8 to somehow activate FLIP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…c-FLIP L , which resembles caspase-8 albeit lacking the proteolytically active cysteine in the caspase homology domain, is able to participate in autoprocessing and membranerestricted activation of caspase-8 (29 -32). c-FLIP L can also be cleaved by caspase-8, and the cleaved p43 form of c-FLIP L has been suggested to promote NF-B signaling (33)(34)(35)(36)(37)(38). In contrast, c-FLIP S , which lacks the caspase homology domain, inhibits binding and oligomerization of caspase-8 in the DISC, thereby preventing the activating cleavage of caspase-8 (29) and generation of the cleaved NF-B-activating fragment of c-FLIP L .…”
Section: Fever-like Hyperthermia Controls T Lymphocyte Persistence Bymentioning
confidence: 99%
“…Functional inactivation of the adaptor protein FADD leads to defective T and B cell proliferation in mice [12,[16][17][18]. Such a proliferative rather than apoptotic pathway might originate from an activated death receptor like CD95 and may be transmitted through FADD and c-FLIP, leading to the activation of the NF-jB and Erk transcriptional pathways [19][20][21][22]. This model is supported by transgenic mice that overexpress FLIP L in T cells [23].…”
Section: Introductionmentioning
confidence: 96%